2016
DOI: 10.1103/physrevb.93.054413
|View full text |Cite
|
Sign up to set email alerts
|

On the ferromagnetic ground state of SmN

Abstract: SmN is a ferromagnetic semiconductor with the unusual property of an orbital-dominant magnetic moment that is largely cancelled by an antiparallel spin contribution, resulting in a near-zero net moment. However, there is a basic gap in the understanding of the ferromagnetic ground state, with existing density functional theory calculations providing values of the $4f$ magnetic moments at odds with experimental data. To clarify the situation, we employ an effective $4f$ Hamiltonian incorporating spin-orbit coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
(93 reference statements)
3
19
0
Order By: Relevance
“…However, there are limited examples for solids with native (“undiluted”) semiconductor ferromagnetism. Only little attention was devoted to semiconductor ferromagnets such as GdN, SmN, EuO, or EuS in the past . When it comes to bulk materials, Europium(II) oxide is the most studied.…”
mentioning
confidence: 99%
“…However, there are limited examples for solids with native (“undiluted”) semiconductor ferromagnetism. Only little attention was devoted to semiconductor ferromagnets such as GdN, SmN, EuO, or EuS in the past . When it comes to bulk materials, Europium(II) oxide is the most studied.…”
mentioning
confidence: 99%
“…however the existence of carrier mediated ferromagnetism remains an open question [56]. Several of the ground state magnetic moments are also in disagreement with theoretical Hund's rule free-ion values [57,58]. Undoubtedly as the experimental picture becomes clearer, this will aid theoretical studies and methods to understand the rich magnetic properties offered by the RENs.…”
Section: Magnetic Properties Of Rare-earth Nitridesmentioning
confidence: 99%
“…Hund's rules are based on empirical observations of the electron interactions and magnetic moments of free ions. They are useful for qualitative analysis, however in general other effects in solids such as the crystal field must be taken into account 4 [57]. The first two rules arise from the Pauli exclusion principle and Coulomb repulsion, and the third is a result of the effects of spin-orbit coupling.…”
Section: Hund's Rules and Magnetismmentioning
confidence: 99%
“…The early research reported the Neel temperature 𝑇 𝑁 was 13 K [118], 15 K [119], or 18.2 K [120]. The antiferromagnetic nature of this material was rejected later once the subsequent measurements of both neutron scattering [121] and recent XMCD studies [122,123] very clearly showed the ferromagnetic nature with a small magnetic moment.…”
Section: Magnetic and Electronic Properties Of Samarium Nitridementioning
confidence: 99%